Clinical Efficacy and Potential Mechanisms of Acupoint Stimulation Combined With Chemotherapy in Combating Cancer: A Review and Prospects - Li, Shanshan; Zhao, Suhong; Guo, Yi; Yang, Yuanzhen; Huang, Jin; Wang, Jiaqi; Lu, Shanshan; Wang, Bin; Chai, Chao; Xu, Zhifang; Chin, Yenlie (Frontiers in Oncology, 2022)
Although chemotherapy is the first-line treatment strategy for a variety of tumors, its side effects have limited its efficacy. This review summarizes the progress on the use of acupoint stimulation to combat chemotherapy-associated side effects, including chemotherapy-induced peripheral neuropathy (CIPN), cognitive impairment (CICI), and gastrointestinal toxicity (GI), as well as myelosuppression and immunosuppression. It was found that acupoint stimulation attenuated CIPN and GI by modulating the 5-hydroxytryptamine system in dorsal root ganglia, the dorsal horn of the spinal cord, and the duodenum by reducing oxidative stress and neuroinflammation. Acupoint stimulation also alleviated GI by activating vagal activity in the nucleus tractus solitarius and promoting the secretion of gastrointestinal neuropeptide hormones. Acupoint stimulation restored both bone marrow hematopoiesis and immune function to combat cancer. In addition, the combination of acupoint stimulation and chemotherapy could inhibit tumor growth by promoting tumor cell apoptosis and the enrichment of chemotherapeutic agents in tumor tissue and by modulating the tumor immune microenvironment and normalizing the vasculature. Multiple evidence also indicates that neuroimmune regulation may be involved in the effects of acupoint stimulation. In conclusion, the evidence suggests that acupoint stimulation can alleviate the side effects of chemotherapy and can also assist chemotherapeutic agents in inhibiting tumor growth, which expands the clinical application of acupoint stimulation in cancer treatment. However, more high-quality clinical studies are needed to confirm the clinical value of acupoint stimulation.